دور الزراعة الحافظة في تحسين بعض خصائص التربة الكيمائية، وغلة القمح الحبية في البيئات المجهدة مائياً - العودة أيمن الشحاذة; نمر يوسف; قنبر أسامة حسين (Latakia University Journal -Biological Sciences Series, 2016)
ﹸنفذت تجربة حقلية، في محطة بحوث ازرع ، بمحافظة درعا في سورية ، خلال الموسمين الزراعيين 2011-2012 /2012-2013، بهدف دراسة دور الزراعة الحافظة في تحسين نوعية التربة، والغلة الحبية لبعض أصناف القمح القاسي (دوما1، ودوما3) ، والطري (دوما2، ودوما4) ، تحت ظروف الزراعة المطرية. وضعت التجربة وفق تصميم القطاعات العشوائية الكاملة العاملية المنشقة – المنشقة ، بواقع ثلاثة مكررات. لُوحظ أنّ محتوى التربة من المادة العضوية كان الأعلى معنوياً خلال الموسم الزراعي الثاني ، تحت ظروف الزراعة الحافظة ، بوجود الدورة الزراعية في حال ترك (100، 75، 50%) من بقايا المحصول السابق، وعند العمق الأول (0 – 20 سم) (1.060، 1.047، 1.053% على التوالي) . وكان متوسط محتوى التربة المائي خلال مرحلة الإزهار الأعلى معنوياً خلال الموسم الزراعي الثاني ، تحت ظروف الزراعة الحافظة بوجود الدورة الزراعية ، وفي حال ترك (100، 75، 50%) من البقايا النباتية ، وعند العمق الثالث (40 – 60 سم) (25.98، 25.79، 25.17% على التوالي). ولوحظ أنَّ متوسط الغلة الحبية كان الأعلى معنوياً خلال الموسم الزراعي الثاني ، تحت ظروف الزراعة الحافظة، في القطع التجريبية التي تضمَّنتْ محصول العدس في الدورة الزراعية، لدى صنف القمح القاسي (دوما1)، وفي حال ترك (50، 100، 75%) من بقايا المحصول السابق (234.60، 228.50، 226.70 كغ. دونم-1على التوالي). A field experiment was carried out in Izra’a Research Station, Dara’a goveronorate, Syria, during the two consecutive growing seasons 2011-2012/2012 -2013. The study investigated the role of conservation agriculture in improving soil quality and the grain yield of some durum (Douma1 and Douma3), bread (Douma2 and Douma4) and wheat varieties under rainfed conditions. The experiment was set according to split-split randomized complete block design with three replications. It was noticed that the soil organic matter content was significantly higher during the second growing season, under conservation agriculture (CA), in the presence of crop rotation, when the percentage of the crop residues left on the soil surface was (100, 75 and 50%) and at soil depth of (0 – 20 cm) (1.060, 1.047 and 1.053% respectively). The soil moisture content during the flowering stage was significantly higher during the second growing season, under CA, in the presence of crop rotation, when the percentage of the crop residues left on the soil surface was (100, 75 and 50%) and at soil depth of (40 – 60 cm) (25.98, 25.79 and 25.17% respectively). The grain yield was significantly higher during the second growing season, under CA, when lentil was included in the crop rotation, for the durum variety Douma1 and when the percentage of the crop residues left on the soil surface was (50, 100 and 75%) (234.60, 228.50 and 226.70 Kg . Dounem-1 respectively).